Emerging drivers of female bladder cancer: a pathway to precision prevention and treatment - Zhang, Jianbin; Jia, Haixia; Han, Hui (Frontiers in Oncology, 2025)
PurposeBladder cancer is a public health concern, with smoking and occupational exposure being major risk factors. However, specific risks in women, particularly hormonal, lifestyle, and environmental factors, are underexplored. This study aimed to assess these risk factors in women, focusing on smoking, occupational exposure, recurrent urinary tract infections (UTIs), body mass index (BMI), menopausal status, and family history of cancer.Materials and methodsThis retrospective cohort study included 850 women diagnosed with bladder cancer (2018–2023) and age-matched controls. Data on smoking, occupational exposure, UTIs, BMI, menopausal status, and family history were collected from medical records: multivariate logistic regression and propensity score matching identified independent risk factors. Subgroup analysis explored interactions between menopausal status and other factors.ResultsSmoking (OR = 2.15, p = 0.002), occupational exposure (OR = 1.89, p = 0.007), and recurrent UTIs (OR = 1.72, p = 0.013) were significant risk factors, particularly in post-menopausal women. Menopausal status amplified the effects of smoking and UTIs but was not an independent predictor. BMI and family history showed no significant associations.ConclusionSmoking, occupational exposure, and recurrent UTIs are key risk factors for bladder cancer in women, especially post-menopausal women, highlighting the need for targeted prevention strategies.